1980
DOI: 10.1161/01.cir.61.6.1165
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane release during pacing-induced angina pectoris: possible vasoconstrictor influence on the coronary vasculature.

Abstract: SUMMARY We developed a radioimmunoassay for plasma thromboxane B,, the metabolite of the coronary vasoconstrictor thromboxane A,. To see if thromboxane A, is produced during myocardial ischemia, we used atrial pacing to study 14 patients with greater than 75% occlusive coronary artery disease proved by arteriography. Paired samples were taken from the coronary sinus (CS) and an artery (A) for lactate and thromboxane B, analysis before pacing. During and after pacing at 140 beats/min, sampling was repeated. Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(44 citation statements)
references
References 29 publications
(3 reference statements)
3
40
0
1
Order By: Relevance
“…The role of TxA2 as a vasospastic agent leading to coronary insufficiency has been examined in humans and it was shown that TxB2 in the coronary sinus increased during angina pectoris electrically induced by tachycardia (Lewy, Wiener, Walinsky, Lefer, Silver & Smith, 1980). The coronary constriction would be located, particularly at the level of the arterioles, as it has been demonstrated in the hamster cheek pouch by the administration of the prostaglandin endoperoxide, PGH2 (Higgs, Cardinal, Moncada & Vane, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The role of TxA2 as a vasospastic agent leading to coronary insufficiency has been examined in humans and it was shown that TxB2 in the coronary sinus increased during angina pectoris electrically induced by tachycardia (Lewy, Wiener, Walinsky, Lefer, Silver & Smith, 1980). The coronary constriction would be located, particularly at the level of the arterioles, as it has been demonstrated in the hamster cheek pouch by the administration of the prostaglandin endoperoxide, PGH2 (Higgs, Cardinal, Moncada & Vane, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…1-5. 25 Several groups of investigators have reported that levels of TXB, the stable metabolite of TXA,, are elevated in coronary sinus blood of patients with variant angina.61 --Other investigators have reported elevated TXB2 levels in coronary sinus blood of patients with coronary artery disease after episodes of spontaneous angina, 17 19 in association with pacing-induced angina, 16 or within 24 hr of an episode of chest pain.27 Elevated BTG levels have been reported in coronary sinus blood of patients with coronary artery disease and have been interpreted as demonstrating abnormal platelet activation in the atherosclerotic coronary circulation. '5 In all these studies, blood samples were collected from the coronary sinus with woven Dacron catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Miller and his group (Kumpuris et al, 1980) reported an increased production of platelet aggregates by dynamic exercise in patients with coronary heart disease. At the same time Lewy et al (1980) demonstrated an excessive release of thromboxane into the coronary sinus of patients with coronary heart disease, during pacing-induced angina.…”
Section: Introductionmentioning
confidence: 91%